2018
DOI: 10.1002/bies.201700132
|View full text |Cite
|
Sign up to set email alerts
|

Primary Cilia Reconsidered in the Context of Ciliopathies: Extraciliary and Ciliary Functions of Cilia Proteins Converge on a Polarity theme?

Abstract: Once dismissed as vestigial organelles, primary cilia have garnered the interest of scientists, given their importance in development/signaling, and for their implication in a new disease category known as ciliopathies. However, many, if not all, "cilia" proteins also have locations/functions outside of the primary cilium. These extraciliary functions can complicate the interpretation of a particular ciliopathy phenotype: it may be a result of defects at the cilium and/or at extraciliary locations, and it coul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 136 publications
0
5
0
1
Order By: Relevance
“…Notably, we reported its interaction with actin through NMIIA, its localization to actin-rich structures [16] and now the interaction of Arl13b with β3-integrin and co-localization with FA components, namely Vinculin and Paxillin. Interestingly, it is now appreciated that many ciliary proteins have other localizations besides primary cilia and that they can play a role in the formation of polarized cellular structures [29]. Furthermore, it was described that FA proteins associate with basal bodies of ciliated cells and form ciliary adhesion complexes that interact with the actin cytoskeleton [30].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, we reported its interaction with actin through NMIIA, its localization to actin-rich structures [16] and now the interaction of Arl13b with β3-integrin and co-localization with FA components, namely Vinculin and Paxillin. Interestingly, it is now appreciated that many ciliary proteins have other localizations besides primary cilia and that they can play a role in the formation of polarized cellular structures [29]. Furthermore, it was described that FA proteins associate with basal bodies of ciliated cells and form ciliary adhesion complexes that interact with the actin cytoskeleton [30].…”
Section: Discussionmentioning
confidence: 99%
“…ERK signaling is crucial for processes ranging from the cellular stress response and cell polarization (including that of the Golgi apparatus and of the centrosome) during migration (Lu and Xu, 2006; Bisel et al, 2008). This is particularly important as cell polarity proteins are key for ciliary health, but conversely their action is also dependent on cilia mediated signaling (Pruski et al, 2016; Hua and Ferland, 2018), and so defects in cell polarity proteins might have self-enhancing effects. The decrease in ERK phosphorylation in WIM cells (Figure 5) might be a result of the WIM cells having a decreased ability to sense the growth factors associated with cilia, resulting in reduced cell proliferation (Schneider et al, 2005, 2010; Sotak and Gleeson, 2012), and which might translate to reduced cell migration capabilities, especially in vivo , where a range of chemical, physical and electrical cues might guide the moving cells.…”
Section: Discussionmentioning
confidence: 99%
“…Thereafter, the same three proteins were once again found during targeted vesicular trafficking to IS. Both of these findings suggested that polarized protrusion structures, such as cilia, growth cones, dendritic spines, ISs, and migration podosomes, might share a similar building design in polarized vesicular trafficking (Finetti and Baldari, 2013;Hua and Ferland, 2018b).…”
Section: Ift Subunits and Synaptic Vesicular Trafficking In Non-ciliamentioning
confidence: 95%